Pregnancy of Simmental-Ongole crossbreed (SimPO) cows inseminated with frozen semen from Simmental and Brahman - Husna, Syaiful; Sutiyono, Sutiyono; Ondho, Yon Soepri (Politeknik Negeri Jember, 2024)
This research aims to determine the pregnancy success of SimPO cows artificially inseminated (AI) with Simmental and Brahman frozen semen. The research was carried out using a survey method, namely in January–April 2023. The research material was 214 SimPO cows inseminated with Simmental and Brahman frozen semen, which was taken using purposive sampling based on complete data on IB implementers. The research parameters were the body condition score (BCS) of the SimPO cows and the intensity of cervical erection during AI and pregnancy. Data analysis was carried out descriptively using percentages, histograms, and polygon graphs. The results of the study showed that the cows who had a BCS of 7, 6, and 5 had mostly moderate quality (++) cervical erection scores of 47.22%, 42.42%, and 40.11%, respectively, while the cows who had a BCS of 4 and 3 were mostly of low quality (+) 53.33% and 53.13%, respectively. The pregnancy percentage of SimPO cows inseminated with Brahman frozen semen was highest at BCS 7 (50.00%), while Simmental frozen semen was at BCS 5 (31.86%). This research concludes that the pregnancy rate of SimPO cows inseminated with Brahman frozen semen is higher than Simmental frozen semen.